PENGALAMAN PERAWAT DALAM MELAKUKAN MANAJEMEN NYERI PADA PASIEN SINDROM KORONER AKUT DI RUANG ICCU - chrisyen damanik (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
Background: The prevalence of Acute Coronary Syndrome in Indonesia increases and is high every year. Pain is a complaint of SKA patients which can be managed by pharmacological and non-pharmacological interventions. Efforts to improve comfort for patients are non-pharmacological, namely the provision of deep breath relaxation, comfortable position, and guide imagery are the main strategies of independent nursing action in accordance with operational standard procedures. Objective: To explore the experience of nurses in performing pain management on patients with Acute Coronary Syndrome in the ICCU Room. Method: Qualitative research with a phenomenological study approach by sampling, purposive sampling technique, which involved 4 participants with seven-day study duration, data collection was done by in-depth interviewing. The criteria includes nurses who work in the Intensive Cardiac Care Unit (ICCU) with working experience of at least three years, graduates of diploma and bachelor degree in nursing and have the competence in handling critical patients; one of them is acute coronary syndrome. The results of the study: Resulted in three themes: 1) Giving non-pharmacological actions only to mild to moderate pain with accompanying Pharmacological therapy. 2) Giving deep breath relaxation, comfortable position, and guide imagery as non-pharmacological actions. 3) Administration of Thrombolytic, Cedocard and Morphine as pharmacological collaborative actions. Conclusion: The experience of nurses in handling pain in acute coronary syndromes in a non-pharmacological way, namely giving deep breath relaxation, comfortable position, and guide imagery along with pharmacological therapy as a collaborative action.